Difference Between Corporate Logistics Management and Defense Logistics Management - Fanema Gabrieli; Hikmat Zakky Almubaroq; Sundring Pantja Djati; Nora Lelyana (CV. AFDIFAL MAJU BERKAH, 2023)
Logistics Management basically starts from logistics management for war. To go to war, you must have good logistics management in order to win the war. Along with the times, logistics management has evolved to be used for a company. Against this background, the title of this study is the difference between corporate logistics management and defense logistics management. The research methodology used in this study is a literature review. The conclusion of this study is that Logistics management in companies with logistics management in defense has the same outline. Basically, logistics management focuses on maintenance planning, workforce and personnel, supply support, equipment support and testing, equipment training and education, technical documentation, computer facilities, contracts, negotiation and Transfer of Storage, Space, Stability and Maintenance. Meanwhile, logistics management in defense focuses on the main areas of logistics and supply chain management in the context of sustainability, inventory management, resilience, procurement, information systems and crisis response.